Circulating Tumor DNA (ctDNA) in Kidney Cancer: A Narrative Review - Wesley Yip; A. Ari Hakimi (Société Internationale d’Urologie Journal)
Circulating tumor DNA (ctDNA) has been investigated as a potential noninvasive biomarker for disease prognostication, monitoring, and treatment selection in various tumor types, including renal cell carcinoma (RCC). In this narrative review, we explore the current methods of ctDNA analysis and the use of ctDNA in both localized and metastatic RCC, focusing on plasma and urine samples. Additionally, we discuss several ongoing as well as upcoming clinical trials that incorporate ctDNA analyses into their study designs and outcomes. Despite the exciting potential of ctDNA in RCC, current assays still face significant limitations in sensitivity and detection limits.